GAMBARAN PERAN TENAGA KESEHATAN DALAM PENANGANAN EFEK SAMPING KB SUNTIK 3 BULAN - PUJILESTARI, EKA RAHAYU; MARDIYANA, MARDIYANA; Hidayatus, Nurul (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2015)
ABSTRACT             Family planning (FP) is a movement to establish a healthy and prosperous families by limiting births. In dealing with the side effects of injecting three months family planning necessary role of health workers in providing a wide range of appropriate treatment side effects experienced. This study aims to determine the role of health workers in handling side effects of injecting 3montsKBPuskesmasNgambon2014.            This research is deskrptif, the survey approach. Total population of 20 respondents, who used a non-probability sampling sampling sampling saturated type. Research variable is the role of health workers in the management of side effects Injectable 3 months. Collecting data using a questionnaire. The results of the analysis of data processing and analysis of data that includes editing, coding, scoring and tabulation.            The results obtained are the majority of respondents have a good role in the management of side effects Injectable 3 months ie 16 respondents (80%).             The conclusion of this research Most of the respondents have a good role in the management of side effects Injectable 3 months. Health workers can be expected as the appropriate service provide duties and functions there by realizing an excellent service to thepatients. Keywords: Roles, health, family planning injection side effect